The Magic school bus at the waterworks - Cole, Joanna; Degen, Bruce (New York : Scholastic Inc., 1986)
When Ms. Frizzle, the strangest teacher in school, takes her class on a field trip to the waterworks, everyone ends up experiencing the water purification system from the inside
AD 660
Keywords: Water treatment plants -- Fiction; School field trips -- Fiction